INTERDISCIPLINARITY AS A PIVOT OF RESEARCH AND PRACTICE: (Proceedings of the ESIDRP International Conference: English Studies at the Interface of Disciplines - Research and Practice (ESIDRP), M. Bekar, K. Maleska and N. Stojanovska-Ilievska (editors), Skopje, 2016) (Journal of Contemporary Philology, 2019)
Review of the Proceedings of the ESIDRP International Conference: English Studies at the Interface of Disciplines - Research and Practice (ESIDRP)
Keywords: proceedings; English Studies; interdisciplinarity